AN INQUIRY OF BATIK MOTIF FOR WEDDING CLOTHES: EDELWEISS FLOWER BATIK MOTIF - Rosalina, Desi; Purnomo, Moh Arif Jati (Institut Seni Indonesia Surakarta, 2024)
The purpose of this art creation is to apply edelweiss motive on party dress suitable for wedding party dress. The method of this artwork creation method consists of expression, technique, and creation. Batik creation process is conducted through combination of handmade and expressive technique by using brush and the proceeded with staining using covering and dying technique. This works consists of two clothing work title, namely “Endless Love” and “This Love” with the motif names for each work being “Edel” and “Weiss”, respectively. The meaning behind the combination of title endless love which means long lasting and “edel” which mean glorious is that the bride’s wedding becomes glorious and eternal. On the other hand, the title this love means that the love is vulnerable if not handled with care and its motif “weiss” means white which is very easily stained. As a result, we conclude that the final result of this artwork creation is suitable for wedding dress.